Rapid hot-pressing compounding method for copper alloy powder and matrix
Through the rapid hot-pressing composite method of copper alloy powder and matrix, the problems of low composite success rate and mold damage of copper alloy materials are solved, efficient and low-cost production of copper alloy materials is achieved, and the quality and conductivity of the product are improved.
Patent Information
- Application Number
- CN202411897989.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has a low success rate when composited copper alloy materials, and due to the difference in expansion coefficients of different solid materials, it is easy to damage the mold.
Adopt the fast thermal pressure composite method of copper alloy powder and matrix. By sawing and cutting copper alloy round rods and car light, combined with the design of graphite molds, and controlling temperature and pressure during the hot pressure sintering process to achieve the copper alloy material material, to achieve the copper alloy material material Efficient compound.
The success rate of the composite of the copper alloy material is improved, the mold damage is avoided, the production process is significantly simplified, the cost is reduced, and the quality and conductivity of the product are improved.
Smart Images

Figure CN119328145A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nonferrous metal material manufacturing, and in particular to a method for rapid hot pressing and compounding of copper alloy powder and a matrix. Background Art
[0002] The production and processing technology of medium and low voltage contacts has become mature, and the optimal ratio has been basically achieved in terms of material selection; however, in order to avoid waste of materials, processes, and energy as much as possible on the basis of meeting product performance, the upstream and downstream supply chains of the products need to be optimized according to the use effect, among which the focus is on material optimization and process optimization; According to the statistics of the number of times the contacts are broken and scrapped, more than 80% of the contact switches are completely scrapped when they are ablated by about 40%, which is equivalent to at least 50% of the height of each contact product being a waste of material that only provides structural support. With the vigorous development of composite technology: electroplating, hot and cold spraying, welding, hot pressing sintering, 3D printing and other technologies can stably complete the composite of two materials, thereby achieving low-cost material replacement of the invalid 50% part of the contact, but the composite cost of electroplating, hot and cold spraying and 3D printing is too high, and welding is because the cost of solder is high, the process is complex and changeable, and the requirements for the material surface are high, otherwise it is easy to have a low brazing rate and form poor welding.
[0003] With the continuous maturity of hot pressing sintering technology, solid + solid, powder + powder or powder + solid can all be used to obtain parts with excellent composite effect and full density. Among them, the composite method of powder + solid has been confirmed as the most suitable low-cost and convenient process for replacing material composite after comprehensively considering factors such as cost and defect rate.
[0004] However, the existing composite method has a low success rate in practice and often damages the mold due to the different expansion coefficients of different solids. Summary of the invention
[0005] The main purpose of the present application is to provide a method for rapid hot pressing of copper alloy powder and matrix composite, aiming to solve the technical problem of low success rate in the prior art when composite alloy materials.
[0006] To achieve the above objectives, the technical solutions adopted in the embodiments of the present application are as follows: In a first aspect, an embodiment of the present application provides a method for rapid hot pressing of copper alloy powder and a matrix, comprising the following steps: After sawing the target copper alloy round rod, a target copper alloy round rod sheet is obtained; one end surface of the target copper alloy round rod sheet is polished, and the other end surface is kept sawed rough surface; Based on the target copper alloy round rod, a target graphite mold is selected; and the target graphite mold is loaded in the order of lower pressure head-graphite paper-target copper alloy round rod sheet-metal powder-graphite paper-upper pressure head, wherein one end surface of the target copper alloy round rod sheet after lathing is facing downward; After the loading is completed, a sintering composite treatment is performed to obtain a composite copper alloy material.
[0007] As some optional embodiments of the present application, the target copper alloy round rod has a diameter of 50 mm-75 mm and a length of 10 mm-40 mm.
[0008] As some optional embodiments of the present application, the roughness of one end surface of the target copper alloy round rod piece that has been subjected to lathing treatment is less than 6.4, and the roughness of one end surface of the target copper alloy round rod piece that has been maintained as a sawn rough surface is greater than 12.5.
[0009] As some optional embodiments of the present application, the sintering composite treatment is carried out in a hot pressing sintering furnace; the temperature of the sintering composite treatment is 750°C-980°C, the pressure of the sintering composite treatment is 35Mpa-65Mpa, and the time of the sintering composite treatment is 3min-20min.
[0010] As some optional embodiments of the present application, the particle size of the metal powder is -60 mesh; The metal powder is any one of simple powder, mixed powder and alloy powder.
[0011] As some optional embodiments of the present application, the composition of the metal powder is any one of pure copper powder, CuCr mixed powder, copper-chromium-zirconium and copper-chromium-niobium; the chromium content in the CuCr mixed powder is 20wt%-50wt%.
[0012] As some optional embodiments of the present application, the weight ratio of the target copper alloy round rod pieces to the metal powder is 1 to 3.
[0013] As some optional embodiments of the present application, after the step of performing sintering composite treatment after the loading is completed to obtain the composite copper alloy material, the following steps are further included: Using a sandblasting machine to perform sandblasting cleaning treatment on the surface of the composite copper alloy material; The sand used in the surface sandblasting cleaning treatment is aluminum oxide material with a particle size of -100 mesh; the pressure of the surface sandblasting cleaning treatment is 5.0 MPa.
[0014] As some optional embodiments of the present application, the brazing rate of the bonding surface of the composite copper alloy material is 100%; and the composite efficiency is 1h / furnace.
[0015] As some optional embodiments of the present application, when the target copper alloy round rod is a Cu rod and the metal powder is a CuAl dispersed copper powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-42Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuAl dispersed copper powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-42Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrZr mixed powder, the electrical conductivity of the composite copper alloy material is 46Ms / m-51Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrNb mixed powder, the electrical conductivity of the composite copper alloy material is 46Ms / m-53Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCr mixed powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-45Ms / m.
[0016] In the current market, many technologies are widely used, but the process scheme proposed in this application has achieved significant simplification in terms of production procedures, and compared with these technologies, it is also simpler and easier in terms of operation process. This makes it particularly suitable for large-scale blank production and manufacturing. Specifically, the target copper alloy round bar is first sawed to obtain the target copper alloy round bar sheet; then, one end face of the target copper alloy round bar sheet is polished, and the other end is kept in the rough state after sawing; then, based on the target copper alloy round bar, a suitable target graphite mold is selected; and the target graphite mold is loaded in the order of lower pressure head-graphite paper-target copper alloy round bar sheet-metal powder-graphite paper-upper pressure head, wherein one end face of the target copper alloy round bar sheet after polishing is facing downward; after loading, sintering and composite treatment are performed to obtain a composite copper alloy material. In the process scheme proposed in this application, the roughness of the contact surface between the base round bar and the powder is designed, and the purpose of such design is to promote the uniform diffusion of the powder during the hot pressing process, so as to achieve a more excellent composite effect. In addition, the smooth design of the contact surface with the mold pressure head is to avoid excessive pressure due to multi-point force during the hot pressing process, thereby preventing unnecessary damage to the mold. Furthermore, the process scheme proposed in this application adopts a composite method of combining solids and powders, which is different from the traditional method of combining solids and solids. The selection of this composite method is based on considerations of the thermal expansion rate of the powder material, because the thermal expansion rate of the powder material is relatively slow and can better match the thermal expansion rate of the solid substrate. Such a match can effectively avoid mold damage caused by excessive differences in the thermal expansion rates of the two solid materials, thereby improving the stability of the production process and the quality of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the process of the rapid hot pressing composite method of the copper alloy powder and the matrix involved in the embodiment of the present application; Figure 2 Schematic diagram of the fixed mold structure involved in the embodiment of the present application; in the figure, 1 represents the lower pressure head, 2 represents the target copper alloy round rod sheet, 3 represents the metal powder, 4 represents the upper pressure head, and 25 represents the outer circle of the grinding tool; Figure 3 Schematic diagram of a special mold structure with an inner ring that can be moved up and down and is involved in an embodiment of the present application; in the figure, 1 represents a lower pressure head, 2 represents a target copper alloy round rod sheet, 3 represents metal powder, 4 represents an upper pressure head, 35 represents a mold lining, 36 represents a lower half outer ring, 37 represents an upper half outer ring, 38 represents a graphite paper layer, and 39 represents an outer wire of the lining; Figure 4 A metallographic image of a composite copper alloy material 50x involved in Example 2 of the present application; Figure 5 This is a metallographic image of the composite copper alloy material 100x involved in Example 2 of the present application. DETAILED DESCRIPTION
[0018] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0019] According to research, Technical Document 1 reveals a preparation technology for a diamond / copper composite material with high thermal conductivity and uniformity, which includes the following steps: pretreatment of diamond, processing of copper foil, assembly of structure and sintering. This technology uses copper foil as the matrix material and diamond as the composite powder, and sintering is performed by combining rapid hot pressing sintering with high-pressure melt infiltration sintering to finally prepare a composite material with ultra-high thermal conductivity. Technical Document 2 describes a preparation method for a copper-based composite material / titanium alloy bimetal, the main steps of which include grinding, pickling and hot pressing sintering of cylindrical rods of WB2 / CuSn10 composite material and TC6 titanium alloy. The product prepared by this method achieves high strength, high wear resistance and light weight in terms of high-pressure plunger pump cylinder materials and processes.
[0020] Both of the above two technical documents adopt rapid hot pressing and sintering composite technology, and are related to copper alloys. However, the proportion of composite materials in Technical Document 1 is less than 20%, and its research and development purpose is not to reduce material costs, and the composite material is not a copper alloy; although Technical Document 2 realizes the composite of two materials, its composite method is a combination of solid and solid, which is different from the solid and powder composite method used in this application. In addition, the solid-solid composite method has a low success rate in practical applications, and due to the difference in expansion coefficients of different solid materials, it usually causes mold damage.
[0021] Based on this, the present application embodiment provides a method for rapid hot pressing of copper alloy powder and substrate. Figure 1 As shown, the following steps are included: Step S10, after sawing the target copper alloy round rod, a target copper alloy round rod sheet is obtained; one end face of the target copper alloy round rod sheet is polished, and the other end face is kept sawn rough surface. The roughness of one end face of the target copper alloy round rod sheet that is polished is less than 6.4, and the roughness of one end face of the target copper alloy round rod sheet that is kept sawn rough surface is greater than 12.5. The diameter of the target copper alloy round rod is 50mm-75mm, and the length is 10mm-40mm.
[0022] Step S20, based on the target copper alloy round rod, select a target graphite mold; and complete the loading in the target graphite mold in the order of lower pressure head-graphite paper-target copper alloy round rod sheet-metal powder-graphite paper-upper pressure head, wherein one end face of the target copper alloy round rod sheet after lathing is facing downward. The particle size of the metal powder is -60 mesh (i.e., the powder under the sieve after sieving with a 60-mesh sieve, that is, corresponding to 15000 / 60=250 microns, and the powder with a particle size less than 250 microns); the metal powder is any one of a single substance powder, a mixed powder and an alloy powder. The composition of the metal powder is any one of pure copper powder, CuCr mixed powder, copper-chromium-zirconium and copper-chromium-niobium; the chromium content in the CuCr mixed powder is 20wt%-50wt%. It should be noted that the weight ratio of the target copper alloy round rod sheet to the metal powder is 1 to 3.
[0023] The target graphite mold includes Figure 2 The fixed mold shown (i.e. the mold with an integral outer ring), or Figure 3 The special mold shown in the figure is movable up and down and has an inner ring (i.e., a mold with a split outer ring); Figure 2 In the figure, 1 represents the lower punch, 2 represents the target copper alloy round bar (the surface in contact with the lower punch is smooth and flat, and the surface in contact with the powder is rough), 3 represents the metal powder, 4 represents the upper punch, and 25 represents the outer circle of the abrasive tool. Figure 3 In the figure, 1 represents the lower pressure head, 2 represents the target copper alloy round rod sheet, 3 represents the metal powder, 4 represents the upper pressure head, 35 represents the mold lining, 36 represents the lower half outer ring, 37 represents the upper half outer ring, 38 represents the graphite paper layer, and 39 represents the outer wire of the lining (used to cooperate with the outer ring wire to adjust the outer ring mold spacing).
[0024] Step S30: After the loading is completed, a sintering composite treatment is performed to obtain a composite copper alloy material. The sintering composite treatment is performed in a hot pressing sintering furnace; the temperature of the sintering composite treatment is 750°C-980°C, the pressure of the sintering composite treatment is 35Mpa-65Mpa, and the time of the sintering composite treatment is 3min-20min.
[0025] After completing the loading step, the present invention further includes: Using a sandblasting machine to perform surface sandblasting cleaning on the composite copper alloy material; In the surface sandblasting cleaning process, aluminum oxide is used as sand material with a particle size of -100 mesh; the processing pressure is set to 5.0 MPa.
[0026] This application shows in detail how to successfully prepare an integrated metal component through the composite technology of metal powder and matrix. During the hot pressing and sintering process, the metal powder end and the matrix are completely combined beyond the traditional welding technology. This combination not only improves the overall performance of the component, but also significantly enhances its structural stability. In addition, this technology avoids the complexity and cost of conventional extrusion forging steps, directly meets the requirements of metal machining, and thus provides a more efficient and economical solution for the production of metal components.
[0027] After the above steps, the brazing rate of the joint surface of the composite copper alloy material can reach 100%, and the composite efficiency is 1 hour / furnace. The electrical conductivity of the composite copper alloy material is closely related to the target copper alloy round rod material and the metal powder material, which is specifically manifested as follows: If the target copper alloy round rod is a Cu rod and the metal powder is a CuAl dispersed copper powder, the conductivity of the composite copper alloy material ranges from 36Ms / m to 42Ms / m; If the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuAl dispersed copper powder, the conductivity of the composite copper alloy material ranges from 36Ms / m to 42Ms / m; If the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrZr mixed powder, the conductivity of the composite copper alloy material ranges from 46Ms / m to 51Ms / m; If the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrNb mixed powder, the conductivity of the composite copper alloy material ranges from 46Ms / m to 53Ms / m; If the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCr mixed powder, the electrical conductivity of the composite copper alloy material ranges from 36 Ms / m to 45 Ms / m.
[0028] To facilitate those skilled in the art to understand the technical solution of the present application, the technical solution of the present application is described in detail below in conjunction with specific embodiments: Example 1 An extruded pure copper round bar with a base of Φ50xL was used, and it was cut into pieces with a height of 20mm using a sawing machine, and one end was polished. The weight of a single piece was 350g, and 176g of -60 mesh CuAl (dispersed copper powder) composite powder corresponding to the single piece was prepared; a fixed mold with an inner hole of Φ50 was used, and the materials were loaded in the order of lower pressure head-graphite paper-target copper alloy round bar sheet-metal powder-graphite paper (the function is to prevent powder leakage)-upper pressure head, and then a hot pressing sintering furnace (or spark plasma sintering furnace) was used for sintering and compounding, the sintering temperature was 800℃, the sintering pressure was 48Mpa, and the insulation time was 15min; after a batch of sintering was completed, the pieces were taken out and the surface graphite paper was cleaned by sandblasting to obtain a composite copper alloy material; then a sample was taken for cross-section metallography to check that the brazing rate of the bonding surface was 100%; the conductivity was directly measured on the sintered surface of the powder using a conductivity meter, and the conductivity was 38Ms / m.
[0029] Example 2 A forged CuCr1 round rod with a base of Φ75xL was used, and it was cut into pieces with a height of 25mm using a sawing machine, and one end was polished. The weight of a single piece was 987g, and 435g of -60 mesh CuAl (dispersed copper powder) composite powder corresponding to the single piece was prepared; a fixed mold with an inner hole of Φ75 was used, and the materials were loaded in the order of lower pressure head-graphite paper-target copper alloy round rod piece-metal powder-graphite paper (the function is to prevent powder leakage)-upper pressure head, and then a hot pressing sintering furnace (or spark plasma sintering furnace) was used for sintering and compounding, the sintering temperature was 850℃, the sintering pressure was 48Mpa, and the holding time was 15min; after a batch of sintering was completed, the pieces were taken out and the surface graphite paper was cleaned by sandblasting to obtain a composite copper alloy material; then a sample was taken for cross-section metallography to check that the brazing rate of the bonding surface was 100%; the conductivity was directly measured on the sintered surface of the powder using a conductivity meter, and the conductivity was 40Ms / m.
[0030] The composite copper alloy material obtained in this embodiment was subjected to metallographic tests at different magnifications, wherein the metallographic image at 50x is as follows: Figure 4 As shown, the 100x metallographic image is as follows Figure 5 As shown. By observing the metallographic structure of the composite surface of the metal powder and the matrix, A. it can be seen that the metal powder and the matrix have achieved 100% bonding from the edge to the center (that is, the brazing rate is 100%); B. it can be seen that the bonding interface between the metal powder and the matrix does not present a straight line on the interception diagram, indicating that the bonding method of the two materials has changed from two planes to countless concave and convex surfaces, which increases the bonding strength; C. it can be seen that the metal powder and the matrix have experienced material immersion mutual penetration, which further improves the bonding strength.
[0031] Example 3 A forged CuCr1 round rod with a base of Φ75xL was used, and it was cut into pieces with a height of 13mm using a sawing machine, and one end was polished. The weight of a single piece was 514g, and 237g of -60 mesh CuCrZr composite powder corresponding to the single piece was prepared; a fixed mold with an inner hole of Φ75 was used, and the materials were loaded in the order of lower pressure head-graphite paper-target copper alloy round rod piece-metal powder-graphite paper (the function is to prevent powder leakage)-upper pressure head, and then a hot pressing sintering furnace (or spark plasma sintering furnace) was used for sintering and composite, the sintering temperature was 900℃, the sintering pressure was 45Mpa, and the insulation time was 10min; after a batch of sintering was completed, the pieces were taken out and the surface graphite paper was cleaned by sandblasting to obtain a composite copper alloy material; then a sample was taken for cross-section metallography to check that the brazing rate of the bonding surface was 100%; the conductivity was directly measured on the sintered surface of the powder using a conductivity meter, and the conductivity was 48Ms / m.
[0032] Example 4 Use a forged CuCr1 round bar with a base of Φ50xL, cut it into 35mm high slices using a sawing machine, and polish one end. The weight of a single slice is 615g. Prepare 350g of -60 mesh CuCrNb composite powder corresponding to the single slice; use a special mold with an inner hole of Φ50 that can be moved up and down and has an inner ring, and follow the order of lower pressure head-graphite paper-target copper alloy round bar slice-metal powder-target copper alloy round bar slice-graphite paper (to prevent powder leakage)-upper pressure head The materials are loaded and then sintered and composited using a hot pressing sintering furnace (or spark plasma sintering furnace) at a sintering temperature of 930°C, a sintering pressure of 50 MPa, and a holding time of 20 min. After a batch of sintering is completed, the pieces are taken out and the surface graphite paper is cleaned by sandblasting, and two pieces of composite copper alloy materials are obtained by cutting in the middle of the powder layer. Samples are then taken for cross-sectional metallographic examination to check that the brazing rate of the bonding surface is 100%. The conductivity is directly measured on the sintered surface of the powder using a conductivity meter, and the conductivity is 49 Ms / m.
[0033] Example 5 A forged CuCr1 round bar with a base of Φ50xL was used, and it was cut into pieces with a height of 25mm using a sawing machine, and one end was polished. The weight of a single piece was 439g, and 330g of mechanical mixed powder for -60 mesh CuCr25 composite corresponding to the single piece was prepared; a special mold with an inner hole of Φ50 that can be moved up and down and an inner ring was used, and the materials were loaded in the order of lower pressure head-graphite paper-target copper alloy round bar sheet-metal powder-target copper alloy round bar sheet-graphite paper (the function is to prevent powder leakage)-upper pressure head, and then a hot pressing sintering furnace (or spark plasma sintering furnace) was used for sintering and composite, the sintering temperature was 815℃, the sintering pressure was 45Mpa, and the insulation time was 15min; after a batch of sintering was completed, the pieces were taken out and the surface graphite paper was cleaned by sandblasting to obtain a composite copper alloy material; then a sample was taken for cross-section metallography to check that the brazing rate of the bonding surface was 100%; the conductivity was directly measured on the sintered surface of the powder using a conductivity meter, and the conductivity was 37Ms / m.
[0034] The composite efficiency of the methods described in Examples 1 to 5 is 1 h / furnace.
[0035] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for rapid hot pressing of copper alloy powder and matrix, characterized in that: The following steps are involved: After sawing the target copper alloy round rod, a target copper alloy round rod sheet is obtained; one end surface of the target copper alloy round rod sheet is polished, and the other end surface is kept sawed rough surface; Based on the target copper alloy round rod, a target graphite mold is selected; and the target graphite mold is loaded in the order of lower pressure head-graphite paper-target copper alloy round rod sheet-metal powder-graphite paper-upper pressure head, wherein one end surface of the target copper alloy round rod sheet after lathing is facing downward; After the loading is completed, a sintering composite treatment is performed to obtain a composite copper alloy material.
2. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The target copper alloy round rod has a diameter of 50 mm to 75 mm and a length of 10 mm to 40 mm.
3. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The roughness of one end surface of the target copper alloy round rod piece after lathing is less than 6.4, and the roughness of one end surface of the target copper alloy round rod piece after sawing is greater than 12.
5.
4. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The sintering composite treatment is carried out in a hot pressing sintering furnace; the temperature of the sintering composite treatment is 750° C.-980° C., the pressure of the sintering composite treatment is 35 MPa-65 MPa, and the time of the sintering composite treatment is 3 min-20 min.
5. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The particle size of the metal powder is -60 mesh; The metal powder is any one of simple powder, mixed powder and alloy powder.
6. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 5, characterized in that: The metal powder is composed of any one of pure copper powder, CuCr mixed powder, copper-chromium-zirconium and copper-chromium-niobium; the chromium content in the CuCr mixed powder is 20wt%-50wt%.
7. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The weight ratio of the target copper alloy round rod piece to the metal powder is 1 to 3.
8. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: After the step of performing sintering and composite treatment to obtain the composite copper alloy material after the loading is completed, the method further includes: Using a sandblasting machine to perform sandblasting cleaning treatment on the surface of the composite copper alloy material; The sand used in the surface sandblasting cleaning treatment is aluminum oxide material with a particle size of -100 mesh; the pressure of the surface sandblasting cleaning treatment is 5.0 MPa.
9. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: The brazing rate of the bonding surface of the composite copper alloy material is 100%; and the composite efficiency is 1h / furnace.
10. The method for rapid hot pressing and compounding of copper alloy powder and matrix according to claim 1, characterized in that: When the target copper alloy round rod is a Cu rod and the metal powder is a CuAl dispersed copper powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-42Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuAl dispersed copper powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-42Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrZr mixed powder, the electrical conductivity of the composite copper alloy material is 46Ms / m-51Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCrNb mixed powder, the electrical conductivity of the composite copper alloy material is 46Ms / m-53Ms / m; When the target copper alloy round rod is a CuCr1 rod and the metal powder is a CuCr mixed powder, the electrical conductivity of the composite copper alloy material is 36Ms / m-45Ms / m.
Citation Information
Patent Citations
Method for producing aluminum composite material
CN101090788A
Connecting method for sintering / welding titanium-steel dissimilar metal
CN103480846A
Composite sintered wear-resistant plate, preparation method and special stirring-mixing device
CN107020382A
Method for preparing laminated composite by spark plasma sintering
CN110465670A
Manufacture of rod-shaped body of composite sintered material
JP1986000506A